Reliability of Cyclotorsion measurements using Scanning Laser Ophthalmoscopy imaging in healthy subjects: the CySLO study. Issue 4 (1st August 2017) - Lengwiler, Fabian; Rappoport, Daniel; Jaggi, Gregor P; Landau, Klara; Traber, Ghislaine L
Abstract : Background/aims: To evaluate inter-rater and intra-rater reliability of objective cyclotorsion measurements obtained in healthy subjects using the Heidelberg Spectralis spectral domain—optical coherence tomography (SD-OCT) device. Methods: In this prospective methodological study, 32 healthy subjects (14 men, 18 women; aged 21–64 years) were enrolled, 31 right eyes were examined and their foveo-papillary angles (FPAs) were measured. The retinal nerve fibre layer (RNFL) programme by Heidelberg Spectralis (Heidelberg Engineering, Heidelberg, Germany) was used to measure cyclotorsion based on the in-built algorithm for the measurement of the FPA on the scanning laser ophthalmoscopy (SLO) image. Repeated scans of the fixating and non-fixating right eye without and with eye tracker each were obtained by three different examiners. Results: The mean FPA measured overall by all three examiners was 6.6°±2.8°. The inter-rater reliability of the measured FPAs using the linear mixed effects model is estimated as rhointer =0.8803. The intra-rater reliability is estimated as rhointra =0.9589. Conclusions: Repeatability of objective cyclotorsion measurements within and between observers using the Heidelberg Spectralis OCT is very high. SD-OCT/SLO imaging is a reliable imaging technique to measure and study cyclotorsion. Clinical trial number: NCT02631369, Results.